Analisis Pengaruh Inflasi Terhadap Pertumbuhan Ekonomi Di Indonesia - Aulia Fitri Rahmi; Ike Nurhaliza; Salsabila Balqis (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Economic growth is an ongoing challenge that every country needs to address so that economic growth results are significant. Starting from the government, it must know how to accelerate economic growth by increasing per capita output in the long term. The research method used is qualitative with a complete data collection. The Indonesian economy from 2018-2019 was relatively stable at a percentage of 3% with balanced economic growth in the range of 5%. However, in 2020 the Covid-19 outbreak caused Indonesia's inflation to decline sharply to 1.68%. So the impact on economic growth in Indonesia fell by -2.07%.